2009
DOI: 10.1007/s10531-009-9668-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of characteristics of butterfly species on the accuracy of distribution models in an arid environment

Abstract: Species distribution models show great promise as tools for conservation ecology. However, their accuracy has been shown to vary widely among taxa. There is some evidence that this variation is partly owing to ecological differences among species, which make them more or less easy to model. Here we test the effect of five characteristics of Egyptian butterfly species on the accuracy of distribution models, the first such comparison for butterflies in an arid environment. Unlike most previous studies, we perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 54 publications
2
22
1
Order By: Relevance
“…Our investigation supports the suggestion that the completeness of sampling with respect to the environmental gradients is more important for performance than sample size [56]. Models trained on the small herbarium dataset outperformed those trained on the large-but-biased NVS dataset, even after correcting for geographical bias: AUC and COR values were higher for the herbarium models, POC curves departed little from the expected line, and errors rates in the North Island were lower (Figure 5).…”
Section: Discussionsupporting
confidence: 84%
“…Our investigation supports the suggestion that the completeness of sampling with respect to the environmental gradients is more important for performance than sample size [56]. Models trained on the small herbarium dataset outperformed those trained on the large-but-biased NVS dataset, even after correcting for geographical bias: AUC and COR values were higher for the herbarium models, POC curves departed little from the expected line, and errors rates in the North Island were lower (Figure 5).…”
Section: Discussionsupporting
confidence: 84%
“…There have been attempts to assess differences among species in the accuracy of their distribution models (Kadmon et al 2003, Berg et al 2004, Seoane et al 2005, Hernandez et al 2006, Newbold et al 2009b). These studies have often found that species that are more narrowly distributed produce more accurate distribution models, possibly because small‐ranged species have better‐defined habitat requirements and tend to inhabit a greater proportion of the suitable environment, or because in species with larger ranges, populations show local adaptation to the environment in different areas (Stockwell and Peterson 2002, Brotons et al 2004, Segurado and Araújo 2004, Hernandez et al 2006, Newbold et al 2009b). On the other hand, effects of range size could be a statistical artefact associated with the use of pseudo‐absence data (Lobo et al 2008).…”
mentioning
confidence: 99%
“…Host plant distributions strongly influence the occurrence and abundance of specialist insect herbivores (Newbold et al., ). However, the results of the present study showed that climatic factors are important in identifying the geographical limitations of the specialist species occurrences.…”
Section: Discussionmentioning
confidence: 99%